A new diatom (Bacillariophyta) species—Fallacia cinariana sp. nov.—from Kaklık Cave in the Western Anatolian Karst Region, Republic of Türkiye - Sömek, Haşim; Hamilton, Paul Brian; Solak, Cüneyt Nadir; Beauger, Aude; Yilmaz, Elif; Sevindik, Tuğba Ongun (Phytotaxa, 2025)
A new Fallacia cinariana sp. nov. is described from a unique extreme microenvironment in the highly calcareous Kaklık Cave, Pamukkale Travertines in the Western Anatolian Karst Region, Türkiye with calcareous (pH 8.2) rich waters. Valves of F. cinariana are small (<15 um), linear to linear-elliptic with rounded ends. As with the type species for the genus (F. pygmaea (Kützing) Stickle & D.G.Mann), the axial area is composed of a narrow raphe sternum and valve face slits/occlusions on either side, 500–900 nm length. The striae are biseriate and form around a small round to elliptic central area. Falacia subhamulata Lange-Bertalot from Europe is considered the closest morphologically aligned species being larger, wider, broader central area, elliptic to round valve face slits/opening, and fewer biseriate striae. Other comparable taxa include Fallacia subhamulata (Grunow) D.G.Mann, F. angarae, Metzeltin, Kulikovskiy & Lange-Bertalot, F. helenensis (Schulz) D.G.Mann, F. lange-bertalotii Reichardt, F. lenzii Lange-Bertalot and F. pseudohelensis Kulikovskiy, Metzeltin & Lange-Bertalot. Among them, Fallacia lange-bertalotii (originally described from the Europe) co-occurs in Kaklik Cave and is similar, but F. cinariana has different morphological characters and distinct valve face slits/occlusions.